2018
DOI: 10.1007/s10198-018-0989-8
|View full text |Cite
|
Sign up to set email alerts
|

Design and effects of outcome-based payment models in healthcare: a systematic review

Abstract: Introduction Outcome-based payment models (OBPMs) might solve the shortcomings of fee-for-service or diagnostic-related group (DRG) models using financial incentives based on outcome indicators of the provided care. This review provides an analysis of the characteristics and effectiveness of OBPMs, to determine which models lead to favourable effects. Methods We first developed a definition for OBPMs. Next, we searched four data sources to identify the models: (1) scientific literature databases; (2) websites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 89 publications
(172 reference statements)
1
42
0
Order By: Relevance
“…Our findings correspond well with the results of a recent review of outcome-based P4P initiatives, which found favorable effects only when P4P was combined with global base payments (Vlaanderen et al, 2019). Conversely, our findings are in contrast with results from prior reviews on the effects of P4P, which did not find convincing evidence for P4P being (cost-)effective in improving value when the underlying, flawed base payment system is left intact (e.g., Eijkenaar, Emmert, Scheppach, & Schöffski, 2013;Mendelson et al, 2017;Vlaanderen et al, 2019). A possible explanation for the latter is that P4P typically concerns a relatively small part of the total provider payment, whereas initiatives included in this article focus on reform of the total payment system.…”
Section: Summary and Discussion Of Main Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings correspond well with the results of a recent review of outcome-based P4P initiatives, which found favorable effects only when P4P was combined with global base payments (Vlaanderen et al, 2019). Conversely, our findings are in contrast with results from prior reviews on the effects of P4P, which did not find convincing evidence for P4P being (cost-)effective in improving value when the underlying, flawed base payment system is left intact (e.g., Eijkenaar, Emmert, Scheppach, & Schöffski, 2013;Mendelson et al, 2017;Vlaanderen et al, 2019). A possible explanation for the latter is that P4P typically concerns a relatively small part of the total provider payment, whereas initiatives included in this article focus on reform of the total payment system.…”
Section: Summary and Discussion Of Main Findingssupporting
confidence: 91%
“…Empirical work supports the theoretical rationale of a two-component VBP model. Vlaanderen et al (2019), for example, conclude that using explicit incentives for (outcome) quality paired with global base payments seems preferred over using explicit quality incentives alone.…”
Section: The Rationale Of Global Base Payments In Combination With Exmentioning
confidence: 99%
“…Kaiser Permanente, a large integrated health system in the U.S., uses internet, mobile, and, more recently, video technology to improve outcomes and increase convenience for its patients. 42,43 In the Netherlands, ParkinsonNet is developing an integrated reimbursement system to assist their network approach of care delivery, which includes many telehealth solutions as video consultations and online platforms for patients. Countries with single payer health systems, like Canada, Norway, or Luxemburg, are also poised to realize the advantages of home-based care for PD.…”
Section: Overcoming Barriersmentioning
confidence: 99%
“…It may be that faced with such a situation, HTA agencies and other healthcare funders will rely more heavily on other coverage decision approaches such as risk sharing arrangements or managed access schemes [45]. These innovative market access policies may be accompanied by innovations in pricing arrangements, including outcome-based payments [46], thereby promoting patient access despite the uncertainty in the evidence base and an aversion to risk at times of financial crisis [47].…”
Section: Adapting To a New Normalmentioning
confidence: 99%